Interface‐Induced Polarization in SrTiO3‐LaCrO3 Superlattices. Issue 10 (29th February 2016) - Comes, Ryan B.; Spurgeon, Steven R.; Heald, Steve M.; Kepaptsoglou, Despoina M.; Jones, Lewys; Ong, Phuong Vu; Bowden, Mark E.; Ramasse, Quentin M.; Sushko, Peter V.; Chambers, Scott A.
Abstract : Epitaxial interfaces and superlattices comprised of polar and non‐polar perovskite oxides have generated considerable interest because they possess a range of desirable properties for functional devices. In this work, emergent polarization in superlattices of SrTiO3 (STO) and LaCrO3 (LCO) is demonstrated. By controlling the interfaces between polar LCO and non‐polar STO, polarization is induced throughout the STO layers of the superlattice. Using X‐ray absorption near‐edge spectroscopy and aberration‐corrected scanning transmission electron microscopy displacements of the Ti cations off‐center within TiO6 octahedra along the superlattice growth direction are measured. This distortion gives rise to built‐in potential gradients within the STO and LCO layers, as measured by in situ X‐ray photoelectron spectroscopy. Density functional theory models explain the mechanisms underlying this behavior, revealing the existence of both an intrinsic polar distortion and a built‐in electric field, which are due to alternately positively and negatively charged interfaces in the superlattice. This study paves the way for controllable polarization for carrier separation in multilayer materials and highlights the crucial role that interface structure plays in governing such behavior. Abstract : Through the tailored growth of alternating positively and negatively charged interfaces, emergent polarization is observed in SrTiO3 ‐LaCrO3 superlattices. A built‐in electric field is predicted via density functional theory and measured experimentally via X‐ray photoelectron spectroscopy. Measurements of Ti cation displacements within oxygen octahedra via X‐ray absorption spectroscopy and electron microscopy demonstrate a polarization comparable to that of ferroelectric BaTiO3 .